2011
DOI: 10.1016/j.alcohol.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased consumption of ethanol and sugar water in mice lacking the dopamine D2 long receptor

Abstract: Individual differences in dopamine D2 receptor (D2R) expression in the brain are thought to influence motivation and reinforcement for ethanol and other rewards. D2R exists in two isoforms, D2 long (D2LR) and D2 short (D2SR), produced by alternative splicing of the same gene. The relative contributions of D2LR versus D2SR to ethanol and sugar water drinking are not known. Genetic engineering was used to produce a line of knockout (KO) mice that lack D2LR and consequently have increased expression of D2SR. KO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…These observations highlighted the divergent nature of the two isoforms. Our results were consistent with the findings of Bulwa et al [68] who reported that both D2L and D2S isoforms played differential roles in alcohol and sugar intakes. On the one hand, Chen et al [4] reported that the specific D2 receptor antagonist, sulpiride, stimulated consumption of ethanol.…”
Section: A Bâ Et Al Journal Of Behavioral and Brain Sciencesupporting
confidence: 83%
“…These observations highlighted the divergent nature of the two isoforms. Our results were consistent with the findings of Bulwa et al [68] who reported that both D2L and D2S isoforms played differential roles in alcohol and sugar intakes. On the one hand, Chen et al [4] reported that the specific D2 receptor antagonist, sulpiride, stimulated consumption of ethanol.…”
Section: A Bâ Et Al Journal Of Behavioral and Brain Sciencesupporting
confidence: 83%
“…First, it should also be noted that baseline binge-like ethanol drinking (in vehicle-treated groups) varied between studies, but were within a range that we and others have similarly observed using DID procedures (Bulwa et al, 2011;Lowery et al, 2010;Sparta et al, 2008). Importantly, ethanol intake levels within this range were associated with BEC levels that were approximately at or above the BEC level consistent with binge drinking (80 mg/dl).…”
Section: Intracerebroventricular Administration Of Selective Y1rmentioning
confidence: 59%
“…Together, these data suggest that RYGB induces transcriptional alterations within brain circuits known to regulate dopamine function, alcohol intake, and reward processes. Notably, decreases in the dopamine signaling in the mesoaccumbens dopamine pathway have been linked to increases in appetitive behaviors, as well as increases in subjective pleasure from the use of dopamine-enhancing substances (Bello et al 2011; Bulwa et al 2011; Volkow et al 1999). …”
Section: Bariatric Surgery As a Risk For Audmentioning
confidence: 99%